Controle de amortecimento de oscilações eletromecânicas utilizando unidades eólicas do tipo DFIG - Barbosa, Matheus Maia Berriel (2017)
The use of renewable energy sources for the production of electric energy is gaining more and more space in the world scenario, due to the great concern with environment, for example. Due to the evolution in technologies and large investments in recent years, the Wind Energy sector is increasingly becoming a competitive and clean alternative for the energy matrices diversification. In this work will be presented aspects related to the participation of wind farms in the control of frequency electromechanical oscillations damping, through the installation of an additional control oscillation via POD (Power Oscillation Damping) in the rotor side converter (active power grid or Reactive) of the DFIG wind units. The simulations were performed through the CEPEL programs: ANAREDE (Analysis of Electrical Networks) and ANATEM (Analysis of Electromechanical Transients) in three test systems.